Maternity leave and its consequences for subsequent careers in Germany - Nele Elisa Franz (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper analyzes the wage development of mothers interrupting their careers, in comparison to the wages of men who do not face a parental interruption. We estimate OLS regression models for different subcategories defined by age and point in time. We use data from the German Socioeconomic Panel from 1984 to 2011, to show that wages and the financial penalty for maternity differ according to the duration of interruption. We find a lower wage penalty in the short run for women interrupting their careers who are legally protected, but merely delayed penalties for the same group in the long run.
Keywords: C21; J13; J24; J31; 330; human capital; parental leave; wages; OLS; Family and networks; gender; labour; income and poverty